CLINICAL COURSE OF RECURRENT APHTHOUS STOMATITIS IN WOMEN OF FERTILE AGE: ETIOLOGICAL FACTORS, SYMPTOMS, AND TREATMENT APPROACHES - Navruzova ugilkhon Orzijon kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Etiology and Pathogenesis The  pathogenesis  of  RAS  involves  a  complex  interplay  of  genetic, immunological,  and  environmental  factors.  It  is  believed  to  be  a  T-cell  mediated immune response against the oral mucosa. Genetic predisposition plays a significant role, with several polymorphisms identified in genes related to immune function, such as  TNF-α,  IL-1β,  and  NOD-like  receptors  In  women,  hormonal  fluctuations, particularly  during  the  menstrual  cycle,  have  been  suggested  to  influence  the occurrence of RAS. A study comparing serum levels of sex hormones in women with RAS  and  healthy  controls  found  significant  differences,  indicating  a  potential hormonal influence on RAS development Other contributing factors include nutritional deficiencies (e.g., vitamin B12, iron, folic acid), stress, trauma to the oral mucosa, certain  medications,  and  systemic  conditions  like  celiac  disease  and  inflammatory bowel disease